2022
DOI: 10.1007/s10639-022-11055-y
|View full text |Cite
|
Sign up to set email alerts
|

Whether to flip Extreme Apprenticeship: which is more effective in programming instruction?

Abstract: Programming knowledge is more important than ever in the digital world. However, teaching programming can be challenging, especially with novice learners. Considerable research has been conducted into the most effective methods for teaching programming. Extreme apprenticeship, a variation of cognitive apprenticeship, is a method that has been used in teaching programming at university level in recent years. Because this method focuses particularly on completing lots of exercises with coaching and guidance, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Researchers aiming to maximise the visibility and impact of their work should consider Academic Medicine as a potential outlet for publication. Previous studies analysing research trends in e‐learning in medical education also identified BMC Medical Education, Academic Medicine, Medical Teacher and Telemedicine and E‐health as the top publication sources (Hopcan et al., 2023; Sweileh, 2021). Choosing the right journal involves considering factors such as the journal's scope, its target audience, the relevance of the research to the journal's focus, and its reputation within the academic community.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers aiming to maximise the visibility and impact of their work should consider Academic Medicine as a potential outlet for publication. Previous studies analysing research trends in e‐learning in medical education also identified BMC Medical Education, Academic Medicine, Medical Teacher and Telemedicine and E‐health as the top publication sources (Hopcan et al., 2023; Sweileh, 2021). Choosing the right journal involves considering factors such as the journal's scope, its target audience, the relevance of the research to the journal's focus, and its reputation within the academic community.…”
Section: Discussionmentioning
confidence: 99%
“…In the flipped environment, students watch pre‐lesson videos, review documents, or find things out about the course content independently. By doing this, learners need to find solutions with the teacher's support [46, 94, 95]. In the online flipped environment, on the other hand, learners communicate with the teacher digitally, and getting feedback is essential for increasing the quality of learning [93].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The use of digital educational resources of online technology in teaching programming improves the quality of training, and motivation promotes the development of project skills and teamwork [4,5,6,7,8]. The quarantine period has shown the possibility of using digital educational resources (DER) in the educational process, however, in the post-quarantine period, the use of DER is optional.…”
Section: Introductionmentioning
confidence: 99%